HOW THE PANDEMIC MIGHT BOOST REDISCOVERING JUDICIAL DEFERENCE TO ADMINISTRATIVE CHOICES AS A POSSIBILITY - DOI 10.5935/2448-0517.20200037 - Valle, Vanice Regina Lirio do (Juris Poiesis - Qualis A3, 2020)
This paper presents initial signs of a new sensibility in the Brazilian Constitutional Court in reassessing the deferential approach when it comes to judicial review over public choices held by the administrative state. Precedents can be presented before the pandemics, and event after, in provisional injunctions held by the Court, considering a normative framework edited to address the health crisis that expanded the deliberative powers of federative entities and administrative agencies. Even though the limited number of rulings prevent classifying those events as a new trend in the Brazilian Constitutional Court, peremptory refusal on the deferential approach is certainly overcome.